Vanuatu : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix summarizes the factors explaining Vanuatu's recent growth performance, which has weakened since the mid-1990s. The paper highlights that Vanuatu's annual rate of growth averaged 3/4 percent during 1997-2001, compared with 4 3/4 percent during 1992-1996. The paper compares Vanuatu's external competitiveness with several other small island economies in the South Pacific region. The paper describes the development and structure of Vanuatu's offshore financial center, examines its macroeconomic impact, and highlights some key recent developments. It also provides a preliminary assessment of the prospects for the sector.